2015
DOI: 10.1186/s13098-015-0077-5
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic variability in normal glucose tolerance women with the previous gestational diabetes mellitus

Abstract: BackgroundWomen with previous gestational diabetes mellitus (pGDM) and postpartum normal glucose tolerance (NGT) may carry impaired islet β cell secretion, insulin resistance and subsequent altered glucose homeostasis. And certain normoglycemic groups at risks of diabetes were presented with elevated glycemic variability. The aim of study was to investigate the glycemic variability in NGT women with pGDM.MethodsTotal 48 NGT women with pGDM (pGDM group) and 48 age- and BMI-matched NGT women without pGDM (contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 34 publications
2
11
2
Order By: Relevance
“…This could explain why SD in this cohort, reported to be 1.5, is larger compared to SD reported in other studies in subjects with normal glucose tolerance (ranged 0.5 -0.9). However, other GV measures were similar to those reported from analysis of other datasets (28,31,(41)(42)(43). The accuracy of the CGM systems used in the study, particularly in the hypoglycemic range, is a further limitation and may affect GV measurements.…”
Section: Discussionsupporting
confidence: 76%
“…This could explain why SD in this cohort, reported to be 1.5, is larger compared to SD reported in other studies in subjects with normal glucose tolerance (ranged 0.5 -0.9). However, other GV measures were similar to those reported from analysis of other datasets (28,31,(41)(42)(43). The accuracy of the CGM systems used in the study, particularly in the hypoglycemic range, is a further limitation and may affect GV measurements.…”
Section: Discussionsupporting
confidence: 76%
“…Kohnert et al (25) showed that glycemic variability correlated with postprandial b-cell dysfunction in patients with type 2 diabetes. Women with previous gestational diabetes mellitus and postpartum normal glucose tolerance showed elevated glycemic variability, which is associated with impaired b-cell dysfunction (26). Furthermore, glycemic variability can be reduced by improving b-cell function with intensive insulin therapy in early type 2 diabetes (27).…”
Section: Discussionmentioning
confidence: 99%
“…The upper and lower bounds of the time in range definition are consistent with the definitions for hypo- and hyperglycemia defined above. For individuals without type 1 diabetes, 70–140 mg/dL (3.9–7.8 mmol/L) represents a normal glycemic range ( 66 ). However, spending most of the day in this range is not generally achievable for people with type 1 diabetes because they do not have physiological insulin secretion ( 67 ).…”
Section: Time In Rangementioning
confidence: 99%